Managerial Learning Behavior and Learning Opportunities within the Learning Organization - Maniam, Vikineswaran A. (2008)
The aim of this study was to determine the relationship between managerial learning and the learning organization. Previous studies have linked managerial learning to career success perception without considering the learning organization, and learning by managers to learning organization, where managerial learning variables and career success perceptions were excluded. This research used the causal modeling research design. A validated questionnaire tested for reliability (α=.9046) via a pilot study was distributed to managers (n=309), who formed the unit of analysis, and working in manufacturing and services based industries in Kuala Lumpur and Selangor. Findings showed that although managers scored highly in expressing their perception on how well the organization they work for measure up as learning organizations, they felt that intrinsic factors such as learning behavior and subjective elements of career success contributed more to the learning of the organization as a whole rather than extrinsic factors such as learning opportunities. The relationship of career success perception, learning behavior and learning opportunities with the learning organization showed strong, moderate and weak, with positive linear relationships respectively. Further analysis on career success perception and the learning organization showed both models as being stable and acceptable. Career success perception mediation between learning behavior and the learning organization was partial whereas that between learning opportunities and the learning organization was perfect. Finally, key fit indices indicated model a fit among the major variables involved in this research.. From the findings of this research several conclusions can be drawn. Firstly, managers’ two main learning behavior were: (i) planned learning, which refers to the ability of managers to take responsibility to do self-directed learning that were job relevant, and (ii) meaning oriented learning, which represents hands-on problem solving with relevant job knowledge, continuously updated via reflection and intense mental processes. However, instruction oriented learning was least preferred, because seeking instructions from top management may be misconstrued as incompetence by the management and the managers, hence negative perception shown towards seeking of top management advice when pacing job related problems. Secondly, the main learning opportunity was the high responsibility and non-authority relationship that gives managers ample opportunities for on-the-job learning. Thirdly, the subjective elements of career success perception, such as the relationship with working colleagues, have strong influence on the learning organization. Finally, the confirmatory factor analysis on learning organization indicated career success perception as its strongest positive influencing variable whereas obstacles were considered as having the main negative influence. These findings would help HRD strategists to plan for more effective managerial learning by reducing the restraining forces, such as negative perception towards instruction oriented learning and obstacles, and developing enabling ones, such as planned learning behavior, to improve the career satisfaction, and learning infrastructure. Consequently, managers can enhance their abilities to manage, direct and facilitate their own learning as well as carrying out an effective role as agents to lead other learners in the organization they work for.